2022
DOI: 10.1088/2053-1591/ac5ef6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the phosphogypsum calcination time on the compressive mechanical properties of phosphogypsum-based composite cementitious materials

Abstract: In this study, phosphogypsum-based composite cementitious materials (PGCMs) were prepared by adding fixed proportions of additives to calcined phosphogypsum (PG). Samples with dimensions of 40 × 40 × 80 mm and 150 × 150 × 300 mm were used to study the effect of the PG calcination time on the PGCM compressive strength, stress–strain relationship, and failure mode and its mechanism. The test results indicated that the PGCM compressive strength gradually increased as the calcination time increased. When the PG ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Longer calcination times have been attributed to improving the material's densification by lowering porosity and boosting uniformity. A high purity end product can result from prolonged hightemperature calcination, which can help to remove volatile or impurity components [24].…”
Section: Crystalline Structure Analysis Of Powdersmentioning
confidence: 99%
“…Longer calcination times have been attributed to improving the material's densification by lowering porosity and boosting uniformity. A high purity end product can result from prolonged hightemperature calcination, which can help to remove volatile or impurity components [24].…”
Section: Crystalline Structure Analysis Of Powdersmentioning
confidence: 99%
“…The phosphogypsum used in the study is produced in Kaiyang, Guizhou province. Based on the existing research results of Zheng et al [35], the phosphogypsum directly obtained from the factory is roasted for two hours at 160 °C for further use. The cement used in this study is conch P.O.42.5 ordinary Portland cement, and its main performance indexes are shown in Table 1.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…It was reported that about 5 tons of phosphogypsum are produced for every ton of phosphoric acid produced. The global annual output of phosphogypsum is about 100–280 million tons, but the recycling rate is only 15% [ 3 ]. At present, the annual emission of phosphogypsum in China exceeds 75 million tons, and the cumulative stockpile has exceeded 500 million tons, but the comprehensive utilization rate is only about 40% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global annual output of phosphogypsum is about 100–280 million tons, but the recycling rate is only 15% [ 3 ]. At present, the annual emission of phosphogypsum in China exceeds 75 million tons, and the cumulative stockpile has exceeded 500 million tons, but the comprehensive utilization rate is only about 40% [ 3 ]. Red mud is a reddish brown alkaline industrial waste discharged during the process of refining alumina from bauxite [ 4 ]; its main components are Fe 2 O 3 , Al 2 O 3 , SiO 2 , NaO 2 , CaO, TiO 2 , etc., and the pH value is 10–13 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%